Transformasi Tradisi Lisan Onduo Ke Bentuk Teater Kontemporer Potatah Petitih Potang - Fadhli, Syahrizal; Yusril, Yusril; Afrizal H, Afrizal H (Institut Seni Indonesia Padangpanjang, 2023)
This article describes the process of creating contemporary theater based on research on the local wisdom of Rokan Hulu, namely an oral tradition called Onduo. Onduo is one of the cultural assets of the Rokan Hulu community, old folklore, so it has a nobility that is passed down. The form of Onduo is a song-like poem with a distinctive Rokan tone and language with swinging tones. Onduo itself contains advice and teachings about life, a hum that is usually conveyed by a mother when she puts her child to sleep. This article explains the research journey and the creative process in transforming Onduo's oral tradition into contemporary theatrical forms based on the power of narrative text, actors' bodily expressions, and artistic elements, including sets, props, lighting, make-up, costumes, as well as music. The theatrical work entitled Potatah Petitih Potang is an attempt to bring back a form of a collective memory of the Rokan Hulu community about Ondua, whose existence today has begun to fade. The hope is that the younger generation can understand values, and messages, which are implemented through narrative texts sung or spoken by actors in the show. TRANSFORMATION OF ONDUO'S ORAL TRADITION INTO CONTEMPORARY THEATER POTATAH PETITIH POTANGAbstrakArtikel ini menguraikan tentang proses penciptaan teater kontemporer yang didasari atas riset tentang kearifan lokal Rokan Hulu, yakni satu tradisi lisan bernama Onduo. Onduo merupakan salah satu kekayaan budaya masyarakat Rokan Hulu, yakni folklore yang sudah berumur, sehingga memiliki keluhuran yang diturunkan. Bentuk Onduo sendiri berupa nyanyian seperti syair dengan nada dan Bahasa Rokan yang khas dangan nada yang mengayun-ayun. Onduo sendiri berisi nasehat dan ajaran-ajaran tentang kehidupan, senandung yang biasa disampaikan oleh seorang ibu dalam menidurkan anak. Artikel ini bertujuan untuk menjelaskan tentang perjalanan riset, dan proses kreatif di dalam mentransfromasikan tradisi lisan Onduo ke bentuk teater kontemporer, bertolak pada kekuatan teks narasi, ekspresi tubuh aktor, dan elemen artistik meliputi set, propeti, pencayaan, rias, kostum, sekalgus musik. Karya teater yang diberi judul Potatah Petitih Potang merupakan usaha untuk menghadirkan kembali bentuk memori kolektif masyakarat Rokan Hulu tentang Onduo, yang eksistensinya pada hari ini sudah mulai pudar. Harapannya, generasi muda mampu memahami nilai-nilai, pesan moral, yang diimplementasikan melalui teks narasi yang didendangkan atau diucapkan aktor di dalam pertunjukan.